Mutation of TRPC6, autism candidate gene, induces hyperexcitability of neurons by reducing store-operated calcium entry (SOCE) - Kyung Chul Shin (13913556) (2023)
Poster by Kyung Chul Shin, Gowher Ali, Houda Yasmine Ali Moussa, Lawrence W. Stanton, and Yongsoo Park (Hamad Bin Khalifa University) Background: Autism spectrum disorder (ASD) is a complex and heterogeneous neurodevelopmental disorder, mainly caused by rare and de novo genetic variants and mutations. ASD co-occurs with comorbid attention-deficit hyperactivity disorder (ADHD) and epilepsy, which are associated with hyperexcitability of neurons. TRPC6 is a candidate risk factor for ASD and implicated in ASD etiology; de novo missense and nonsense mutations in TRPC6 associated with ASD etiology have been reported. Loss-of-function mutations in TRPC6 reduce calcium influx in human induced pluripotent stem cell (hiPSC)‐derived neurons cell and TRPC6 knockdown (KD) in Drosophila as a ASD animal model causes autism-like behavioral deficits and leads to the hyperactivity phenotype. However, the pathophysiology underlying hyperactivity phenotype caused by TRPC6 mutations in ASD is unclear and mains poorly understood. Objective: We aim to study novel pathophysiological mechanisms of ASD using human pluripotent stem cell technology that offer a platform to model pathology of ASD. Methods: Using hiPSC‐derived cortical neurons, single cell calcium imaging, and electrophysiological recording, we study how TRPC6 knockout (KO) leads to hyperactivity of neurons. Results: We show that TRPC6 KO reduces store-operated Ca2+ entry (SOCE) signaling and leads to hyperexcitability of neurons by increasing action potential frequency and network burst frequency. Our data show the molecular and cellular pathophysiology underlying hyperactivity of ASD individuals, and TRPC6 KO hiPSC-derived cortical neurons can be a good model to study hyperactive behavior of ASD. TRPC6 KO neurons will be used to screen therapeutics that rescue SOCE and reverse hyperexcitability. Conclusion: Our data unveil the molecular and cellular pathophysiology underlying hyperactivity of ASD individuals and TRPC6 KD hiPSC-derived cortical neurons as a platform to model neuropathology of ASD will pave the way for further studies to discover therapeutics for intervention of ASD.